Digital Capabilities, Product Innovation, and Competitiveness of Creative Economy MSMEs in Makassar City with Policy Support as Moderation Variables - Natsir, Uhud Darmawan (CV. Lafadz Jaya, 2026)
Background: Digital transformation has fundamentally changed the competitive landscape of businesses, especially for MSMEs in the creative economy sector. In the framework of the Resource-Based View (RBV), digital capabilities are seen as strategic resources that determine sustainable competitiveness. The city of Makassar as the center of economic growth in the Eastern Indonesia region is a relevant context to study this phenomenon. Objective: This study aims to examine the influence of digital capabilities on the competitiveness of creative economy MSMEs in Makassar City, with product innovation as a mediation variable and government policy support as a moderation variable. Methods: The study used a quantitative approach with an associative-explanatory design and a moderated mediation model. Data was collected from 285 creative economy MSME respondents through purposive sampling and analyzed using SEM-PLS.Results: Digital capabilities have a positive and significant effect on the competitiveness of MSMEs, both directly and through the mediation of product innovation. Policy support has been proven to moderate the relationship between digital capabilities and the competitiveness of MSMEs, although business actors' perceptions of their effectiveness are still at a moderate level. All constructs meet the criteria for convergent validity with an AVE value above 0.50.Conclusion: Digital capabilities are strategic resources that encourage product innovation and increase the competitiveness of creative economy MSMEs. This research makes a theoretical contribution by integrating policy moderation into the mediation model of digital capabilities product innovation competitiveness in the context of MSMEs in Eastern Indonesia.